1982
DOI: 10.1021/ma00230a087
|View full text |Cite
|
Sign up to set email alerts
|

Optical anisotropies of model analogs of polycarbonates

Abstract: Depolarized light scattering and electric birefringence have been used to evaluate the optical anisotropy tensors for dimethyl carbonate, methyl phenyl carbonate, diphenyl carbonate, and 2,2-diphenylpropane. Rotational potentials about the phenyl axes in diphenyl carbonate and in diphenylpropane are estimated from force field calculations of interactions between nonbonded atoms. Rotations of the same sign » |46°| of the phenyl groups in diphenylpropane and uncorrelated rotations ~|46°| about carbonate bonds ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 11 publications
11
56
1
Order By: Relevance
“…However, the above' experimental values for the activation energy can perhaps be accounted for by combining the energy barrier of -2 kcal mol-' mentioned above for the carbonate group at [ = 90" and the barrier for the phenyl rotation discussed in the next section. The results reported by Flory and co-workers (15) show that with the same geometrical parameters (Set II), and the Hill's function, the minimum occurs at [ = 45" with B = 2 kcal mol-I. However, according to our calculations shown in Although intuitively one would expect the minimum to occur at (+,$) = (60°,600), the shifts of the minima from such a position in Figs.…”
Section: The Carbonate Groupsupporting
confidence: 57%
See 3 more Smart Citations
“…However, the above' experimental values for the activation energy can perhaps be accounted for by combining the energy barrier of -2 kcal mol-' mentioned above for the carbonate group at [ = 90" and the barrier for the phenyl rotation discussed in the next section. The results reported by Flory and co-workers (15) show that with the same geometrical parameters (Set II), and the Hill's function, the minimum occurs at [ = 45" with B = 2 kcal mol-I. However, according to our calculations shown in Although intuitively one would expect the minimum to occur at (+,$) = (60°,600), the shifts of the minima from such a position in Figs.…”
Section: The Carbonate Groupsupporting
confidence: 57%
“…The geometrical parameters derived by Dulmage et al (14) are not used here. Comparing them with the parameters reported by Erman et al (15), it is found that there are appreciable differences in the bond angles of the carbonate group as well as the 2,2-diphenyl propane segment. The bond angles in the phenyl group, for example, vary from 120" to as small as 1 1 1.8", and a pronounced nonplanarity of the phenyl is indicated.…”
Section: 39mentioning
confidence: 51%
See 2 more Smart Citations
“…Figure 3 shows the chemical configuration of a polycarbonate segment and identifies the rotation angles. Analyses are available [15,[21][22][23][24][25]] based on energy calculations and diffraction analysis of the glass and of the crystalline form of both the polymer and of low molecular weight analogues. They indicate that the carbonate group is trans-cis and that the chain, considering virtual phenylene bonds, is essentially a planar zig-zag.…”
Section: Methodsmentioning
confidence: 99%